Gene variants of adhesion molecules act as modifiers of disease severity in MS. Issue 4 (July 2017) - Dardiotis, Efthimios; Panayiotou, Elena; Provatas, Antonios; Christodoulou, Kyproula; Hadjisavvas, Andreas; Antoniades, Athos; Lourbopoulos, Athanasios; Pantzaris, Marios; Grigoriadis, Nikolaos; Hadjigeorgiou, Georgios M.; Kyriakides, Theodoros
Abstract : Objective: To assess the potential effect of variants in genes encoding molecules that are implicated in leukocyte trafficking into the CNS on the clinical phenotype of multiple sclerosis (MS). Methods: A total of 389 Greek MS cases and 336 controls were recruited in 3 MS centers from Cyprus and Greece. We genotyped 147 tagging single nucleotide polymorphisms (SNPs) in 9 genes encoding for P-selectin ( SELP ), integrins ( ITGA4, ITGB1, and ITGB7 ), adhesion molecules ( ICAM1, VCAM1, and MADCAM1 ), fibronectin 1 ( FN1 ), and osteopontin ( SPP1 ) involved in lymphocyte adhesion and trafficking into the CNS. Clinical end points of the study were age at MS onset and MS severity as measured by the Multiple Sclerosis Severity Score. Permutation testing was applied to all analyses. Results: SNPs rs6721763 of the ITGA4 and rs6532040 of the SPP1 were found to significantly influence disease severity (permutation p values: 3.00e-06 and 0.009884, respectively). SNP rs1250249 of the FN1 had a dose-dependent effect on age at disease onset (permutation p value: 0.0002). Conclusions: This study provides evidence implicating variants encoding adhesion molecules, responsible for lymphocyte adhesion and trafficking within the CNS, as modifiers of MS disease severity. These genetic biomarkers, which can be available at the time of diagnosis, may be used to assess the biological aggressiveness of the disease and thus guide decisions on treatment.